MIHAIL MANICATIDE – THE MENTOR AND FOUNDER OF ROMANIAN PEDIATRICS - Valeriu Lupu (Romanian Journal of Pediatrics, 2015)
Professor Mihail Manicatide is one of the coryphaei of Romanian medicine, whose contribution to the development of the Romanian medical sciences places him amongst the great personalities, school founders like: Nicolae C. Paulescu, Victor Babes, Ion Cantacuzino, Gheorghe Marinescu etc. Founder of the Romanian school of pediatrics by creating the Pediatrics Schools of Iasi and Bucharest, founder of scientific pediatrics as an approach to child pathology, where the laboratory and clinical research are a natural combination, author of the first pediatrics and child therapeutics treaties, will establish in 1929 the Romanian Society of Pediatrics, a science forum that encapsulates the whole pediatrics thought and practice. Student and disciple of the great scholar that was Victor Babes, knowledgeable of the French and German school of pediatrics through their great personalities, Mihail Manicatide will abide by the principles of honesty, devotion and full dedication to the mission he assumed. A convinced follower of preventive medicine, he managed to imprint the social aspect of the pediatric practice, essential for quality medicine, and he had numerous initiatives in the field of child protection. Unfortunately, posterity rarely evokes his true value and importance, for this reason we fulfill a duty of honor by presenting him at his true dimension.